Iodine's Role in Public Health: Review (The Peerian Journal, 2024)
Iodine is one of the essential micronutrients in the formation of thyroid hormones in the body, and its deficiency causes pathological problems due to insufficient production of this hormone. The aim of this article is to review important topics related to iodine deficiency and its impact on public health. Iodine deficiency is the main cause of endemic goiter, and eating some foodstuffs in quantities exceeding the permissible amounts may interfere with the absorption of iodine in the thyroid gland. Hypothyroidism caused by iodine deficiency early in life can irreversibly impair neuromotor development, leading to poor cognition and growth in children. The prevalence of iodine deficiency disorders worldwide occurs mostly in low- and middle-income countries. A healthy, balanced diet is the ideal solution to provide sufficient iodine. The most common foods that contain iodine are dairy products, seafood, and iodized salt